P82 What do phase 1 microbicide trial participants really think? Are they "only in it for the money?". (23rd May 2012) - Morris, G; Douglas, S; Woodhall, S; Lacey, C
Abstract : Background: Early-phase trials require multiple visits and procedures, which can lead to difficulties with recruitment and compliance. Aims: To explore participants' experience of, and motivation for, taking part in a study of the safety and pharmacokinetics of an HIV microbicide. Methods: 28 women completed eight study visits including pelvic examinations, colposcopy, vaginal sampling (clinician performed and self-taken aspirate) and semi-structured, qualitative interviews. Additional requirements included daily vaginal gel use (12 doses) and sexual abstinence (16 days). Interviews were audio-recorded, transcribed, and analysed using a framework approach. Results: Although renumeration was given by 64% of women as the main or a contributing reason for participating, 71% also stated that they had an interest in HIV or saw the value in the research. 46% volunteered after hearing positive reports from other participants. Difficulties included speculum examinations, sampling, and fitting study visits and gel use into a normal routine. Problems with self-sampling were identified by 12 women, including discomfort and concern about obtaining an adequate sample. 10 participants reported a preference for self-sampling, 11 for clinician sampling. Compliance with gel use was high. Leakage was common but varied with position and depth of insertion. Four women found abstinence difficult. Being single, or discussing the study with partners before enrolment made abstinence easier. Conclusion: Qualitative interviews in early-phase trials capture useful additional information and help determine acceptability of procedures and products. Healthy subjects commonly have multiple non-exclusive reasons for participating in research. Understanding participants' motivation and experiences can aid recruitment and facilitate compliance with study requirements.